If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(x + 1) = 4(x + -1) Reorder the terms: -8(1 + x) = 4(x + -1) (1 * -8 + x * -8) = 4(x + -1) (-8 + -8x) = 4(x + -1) Reorder the terms: -8 + -8x = 4(-1 + x) -8 + -8x = (-1 * 4 + x * 4) -8 + -8x = (-4 + 4x) Solving -8 + -8x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -8 + -8x + -4x = -4 + 4x + -4x Combine like terms: -8x + -4x = -12x -8 + -12x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 -8 + -12x = -4 + 0 -8 + -12x = -4 Add '8' to each side of the equation. -8 + 8 + -12x = -4 + 8 Combine like terms: -8 + 8 = 0 0 + -12x = -4 + 8 -12x = -4 + 8 Combine like terms: -4 + 8 = 4 -12x = 4 Divide each side by '-12'. x = -0.3333333333 Simplifying x = -0.3333333333
| -10(s+3)=-43 | | -(c+6)=1 | | 2(x-4)+3(2-x)+2x+2= | | 7(2l+8)=122 | | 2x-45=90 | | X^5=230 | | x^3-27x^2+12=0 | | 0.43=0.0814ln(x)+0.3357 | | 3sin(x)-2cos(x)=0 | | a-2a-3=0 | | -3y=5t | | x+10-16=1 | | 3*b-b*(-3)+3*(-b)= | | 3X-21=4X-36 | | Ln*(x-4)+ln*(x-7)=ln*18 | | 3xb-bx(-3)+3x(-b)= | | 1/3k-1=4/6 | | In*(x-6)+In*(x-4)=In*15 | | 6x-9-4x=13 | | (4y+7)(4-y)=0 | | q(z)=pz+b | | ln*(x-5)+ln*(x-8)=ln*28 | | x-1/5=3-(x-9)/2 | | (150-80/1-x)2x=0 | | 40-(5)x=8+x | | (5-3x)2x=0 | | (4g-2)*(4g-2)=4 | | 3(2m-8)-4m=20 | | 2sinx=5+cosx | | 4.5=4t^2 | | 7x^2+7x=9 | | cos7x=cosx/3 |